An Assessment of the integration of Palliative Care in the Health System of the Cape Metro District of South Africa - Arendse, Juanita (Department of Public Health and Family Medicine, 2024)
Background Palliative Care (PC) is a neglected yet core component of health care in the public sector. It embodies holistic, people-centred, compassionate care, focussing on vulnerable patients, and their families, with life threatening illness, to enhance their quality of life. Globally and in South Africa (SA), it has been delivered by non-governmental organisations (NGOs) such as hospices. However, in SA in 2017, the National Policy and Strategy for Palliative Care (NPSFPC) prescribed its integration into the public sector health care system. Following the NPFSPC, the Western Cape provincial health and wellness department initiated a PC service without additional resources prior to the COVID-19 pandemic. Aim - The aim of the study is to investigate factors that influenced integration of PC into the Metro Health Services within the Cape Metro District (CMD). Four complementary studies were conducted to assess integration of PC within the CMD public sector health system. Firstly, the state of PC service delivery was compared 24-months on from baseline. Then, perceptions of and identification of enablers and obstacles to PC among managers and external stakeholders at the beginning of the initiative were elicited, followed by the experiences of implementers, and finally the experiences of beneficiaries of the services. Methods - Study methods were informed by a framework for analysing integration of targeted interventions into health systems, for both data collection and data analysis. A mixed methods approach was used - a document review, quantitative before and after implementation design, complemented by qualitative research that aimed to understand the underlying issues. These comprised a review of personnel and services in the public health sector, PC ICD 10 data codes and morphine utilisation data, and 16 individual interviews and 13 focus group discussions. It utilised the conceptual framework of Atun et al. for analysing integration of targeted interventions into health systems. Findings -The project increased the availability of CMD PC services and resulted in a partial integration of PC into primary care services. There was clear commitment to improve the pattern and rate of adoption of PC, towards eventual assimilation into the health system functions. The document analysis found that governance arrangements included PC in provincial priority setting and operational service planning, indicating the growing importance given to thiservice. The COVID-19 pandemic had exposed the gaps in PC provision but had also highlighted the need and opportunities for PC as an essential service. The quantitative data analysis of morphine utilisation and PC attendance did increase, but this was not statistically significant. Managers' and external stakeholders' commitment to a compassionate health system that is patient centred, enabled its integration. Additionally, a PC capacitated workforce, together with leadership and governance that supports PC integration is required. Two years after policy implementation, managers' reflections indicate that a more inclusive policymaking process, together with creating awareness about PC among both staff and communities served, which focussed on reducing stigma, were important. Furthermore, to take PC integration forward requires pandemic planning that includes PC, strategic partnerships, and leading with care and compassion. Front line health providers, the street level bureaucrats (SLBs) in health systems, need to be heard in service package policy making. They need visible managers and senior leadership to support PC service on the frontline. A multi-disciplinary team approach, facilitating inter- professional support, are essential to support integration of PC. Patients and family receiving PC services needed support for family caregiver, and better pain and symptom control. They were frustrated by delayed referrals and service waiting times, and their inability to access other MDT members, particularly during the COVID-19 pandemic. Conclusion and recommendations The study demonstrates that robust well-consulted policymaking processes are required to ensure that policy is relevant and includes the voice of SLBs in clinical policy decision-making. They require leadership that is compassionate and visible together with clear guidance on service changes that facilitate inter-professional support and involves community health workers. Health system changes, such as standardised referral systems that include PC are required which allow flexibility when considering facility and patient context. Training was a gap, and capacity building for PC service provision should be included in undergraduate training for all health professionals, coupled with in-service training for employed health professionals. Furthermore, stakeholder engagements towards collaboratively creating public awareness about PC that drives the compassionate care agenda while addressing social determinants of health, is essential to embed and mainstream the service, support staff, patients and family caregivers. Finally in the light of the experience of the COVID-19 pandemic, planning for future pandemics needs to include ongoing care for PC patients as well as factoring in an increased demand